Design of a controller of an exoskeleton for the shoulder rehabilitation of the upper limb - Nayen, Md. Julkar (Kulliyah of Engineering, International Islamic University Malaysia, 2019)
Current physical rehabilitation techniques for stroke recovery use a manual hands-on approach which has limitation of dependence on human assist. Thus, physiotherapy treatment is inadequate in usage, is profoundly hypothetical and can just utilize a number of fundamental activities. Extended endeavors are being made in the innovative work of rehabilitation robots to address these issues. This research investigates the utilization of an exoskeleton robot for physical rehabilitation of the human upper limb. This work presents the early results regarding the design, construction and control of a robotic hand. Impedance control includes activation of the exoskeleton to move the patient's arm through a predetermined trajectory with a high degree of reliability. The concept of 4R shoulder mechanism with kinematics and dynamic analysis of the exoskeleton was developed mathematically and minimum jerk trajectory was planned with CAD software and simulated using Simulink/Matlab in order to validate an impedance and a PID controller for the shoulder movements of the upper limb as projected in this work. Prototype was designed and developed. Finally, controller was mounted and tested on the prototype. Several experiments were conducted so that the proposed method is verified. From the experiments different rehabilitation motions were achieved with a minimum joint position error of 1 degree which finally satisfies the upper limb rehabilitation application requirements.